Competitive Advantage dalam Peningkatan Mutu Pendidikan Islam: (Studi Kasus pada SMAS Islam Sunan Gunung Jati Ngunut Tulungagung) - Zamahsari Abdul Azis; Prim Masrokan Mutohar; Agus Eko Sujianto (Lembag, 2024)
This research aims to describe competitive advantage which focuses on competitive strength, competitive area, and competitive results in improving the quality of Islamic education at SMAS Islam Sunan Gunung Jati Ngunut Tulungagung. This research uses a qualitative approach with a field study type. The method used in this research is descriptive with data collection techniques using in-depth interviews, observation, and documentation. The data analysis technique in this research was carried out in three stages, namely data condensation, data presentation, and verification of findings. Checking the validity of data in research uses extension and persistence of participation. The results of this research show that (1) the competitive strength of SMAS Islam Sunan Gunung Jati Ngunut Tulungagung refers to its advantages and differentiates it from competitors, thereby providing a competitive advantage in the market. (2) The competitive area includes certain market segments or the entire market targeted by educational institutions. (3) Then the competitive results are reflected in the institution's ability to attract prospective students, provide quality education, and meet the needs of students and parents effectively.